Income-expense Analysis in Medical Institutions-Application in Turkey - Dayi, Faruk; Esmer, Yusuf; Civan, Mehmet (Elsevier BV, 2016)
AbstractIn medical sector a huge reform has started by health transformation program came into effect in 2003 in Turkey. The primary purpose is to provide to level up the service standard of the public hospitals with the same one of the private hospitals, even maintaining this service standard increasingly. The Public Hospitals Association was established for levelling up the service quality of the public hospitals and optimization of their financial capabilities in 2011. So, the necessary infrastructure is prepared for both serving the patients and making profit. Therefore, financial statements and various statistical information of 10 public hospitals in Zonguldak have been analysed. The implementation consists of data belong to 2009-2012 period. According to findings obtained the income of the public hospitals increased between 2009-2012 periods. However, the expenses have increased more.
Keywords: Cost management; Health businesses; Public hospital administration; Financial management; Financial analysis; 3. Good health